Jovens da Escola do Campo: tessituras híbridas com a cultura do campo e da cidade - Sousa, Kamila Costa de (2020)
This doctoral dissertation has the general objective of understanding how young students of a rural school interact, assimilate and resignify, in their daily school practices, the peasant culture that is proposed by rural education. Its research focus is the School of Rural Education Filha da Luta Patativa do Assaré, located in Santana da Cal Settlement, in the rural area of the municipality of Canindé, which started its activities in 2016. The subjects of this research are 10 young students of the school, who live and build their life projects in their territories and developed meanings for their school experience. The research is based on the theoretical and methodological approach of qualitative research in education (BOGDAN; BIKLEN, 1994), guided by the contributions of multisituated ethnography (MARCUS, 1999), having in view the construction of the object and the realization of field work. Participating observation, field diary and semi-structured interview were used as procedures. Rural Education (CALDART, 2002; 2012) and rural schools in Ceará represent the conquest of peasant social movements, especially the Landless Rural Workers Movement (Movimento Sem Terra - MST), for the right to an education contextualized with the reality of the countryside. Because it is connected to the territory to which belongs, the school under research has as one of its formative matrices the Peasant Culture, which for some young people means ―valuing who we are‖, besides enabling the construction of new perspectives on life in the countryside and possibilities of staying in that territory. For others, it is revealed as a conflicting relationship of staying in that space and developing work in peasant family agriculture. The educational praxis of rural education/rural school announces the possibility of building a new reality for rural areas in Brazil, in which productive work and peasant culture can be understood as foundations for another way of producing life and food. The research reveals that these young students, in their daily school practices, re-elaborate ways of reexistence of youth culture (PAIS, 2003), from the adhesions and conflicts that emerge in their hybrid cultural practices (GARCÍA CANCLINI, 2011) in school. They express ways of proceeding and tactics (CERTEAU, 2013) when they manage to resignify the culture instituted by the rural school and produce meanings for their ways of life.